Method Development and Optimization to Increase Solubility of Poorly Water-soluble Antipsychotic Drug Haloperidol: A Novel Hydrotropic Techniques for Improving the Bioavailability of Biopharmaceutics Classification System Class II Drug - Patidar, Priyanka (International Journal of Pharmaceutical & Biological Archive, 2026)
Haloperidol, a first-generation antipsychotic drug classified under Biopharmaceutics Classification System Class II, suffers from poor aqueous solubility, which critically limits its oral bioavailability and therapeutic performance. To address this challenge, a novel hydrotropic solubilization approach was employed using sodium salicylate as the hydrotropic agent. The study aimed to enhance the solubility and dissolution profile of haloperidol by formulating hydrotropic solid dispersions and optimizing key formulation parameters. A 32 full factorial design was applied to assess the influence of drug-to-carrier ratio and solvent volume on drug content and in vitro release. Among nine formulations developed, F5, prepared with a 1:2 drug-to-carrier ratio and 10 mL solvent volume, exhibited optimal performance with high drug content and rapid release. Fourier transform infrared spectroscopy confirmed the absence of chemical interaction between Haloperidol and the hydrotropic agent. In vitro dissolution studies demonstrated significantly enhanced drug release from the optimized formulation compared to the pure drug and physical mixtures. Accelerated stability studies conducted over 3 months at 40°C and 75% RH confirmed the physical and chemical stability of the optimized formulation. Statistical validation using one-way analysis of variance followed by Tukey’s post hoc test revealed that improvements in drug release were statistically significant (P < 0.05). The study successfully demonstrates the potential of hydrotropic solid dispersion as a simple, effective, and scalable technique for improving the bioavailability of poorly soluble antipsychotic drugs like Haloperidol, laying a strong foundation for further development and clinical application.